2007
DOI: 10.1200/jco.2006.10.4703
|View full text |Cite
|
Sign up to set email alerts
|

BRCA1 and BRCA2 Genetic Testing in Hispanic Patients: Mutation Prevalence and Evaluation of the BRCAPRO Risk Assessment Model

Abstract: Deleterious BRCA1 and BRCA2 mutations occur at considerable frequency within the Hispanic population, many of which have been identified previously in other ethnic populations. The BRCAPRO model appears to perform equally well in Hispanics as in whites.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
37
1
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(44 citation statements)
references
References 39 publications
5
37
1
1
Order By: Relevance
“…All models showed a higher mutation probability in BRCA1 mutation carriers than that in non BRCA mutation carriers. The mean probabilities for BRCA1 mutation positive individuals predicted by BRCApro in this study were lower than what have reported previously in other ethnic, which ranged from 26 to 78% by BRCApro [11,20], and was similar to Vogel's report [22]. Of BRCA2 mutation carriers, the pre-test probabilities were not different from that of non BRCA mutation carriers.…”
Section: Discussionsupporting
confidence: 81%
“…All models showed a higher mutation probability in BRCA1 mutation carriers than that in non BRCA mutation carriers. The mean probabilities for BRCA1 mutation positive individuals predicted by BRCApro in this study were lower than what have reported previously in other ethnic, which ranged from 26 to 78% by BRCApro [11,20], and was similar to Vogel's report [22]. Of BRCA2 mutation carriers, the pre-test probabilities were not different from that of non BRCA mutation carriers.…”
Section: Discussionsupporting
confidence: 81%
“…Although relatively rare in our sample, this is the most commonly reported African founder [8,9]. The mutation has been reported in a family of Bahamian descent living in Florida [19], a French family from the Ivory Coast [27], and in many African-Americans families [8, 9,11,12,19,26,28]. The mutation was recently reported in a Mexican woman [29] and in three other patients of Latin American/ Caribbean background in the BIC database [20].…”
Section: Discussionmentioning
confidence: 93%
“…Several prevalence surveys of BRCA mutations have been conducted among women of African or AfricanAmerican descent [8][9][10][11][12][13][14][15]. These studies show that the spectrum of mutations among Africans is different from that of white women, but in most studies, the overall prevalence of mutations is comparable.…”
Section: Introductionmentioning
confidence: 99%
“…However, a lack of basic information about the prevalence and spectrum of BRCA mutations hinders research progress on the etiology (6) and risk evaluation of model of breast cancer prevention in China. Additionally, because of the large presence of ethnic-specific contexts (11)(12)(13)(14), the Western risk evaluation models do not apply well to China. Therefore, the following paper assembled a wide-range clinic-based cross-sectional study of hereditary risk among BC patients, who were representative for BRCA mutations study.…”
Section: Introductionmentioning
confidence: 99%